Spol in starost učencev kot dejavnika razlik v učiteljevi naklonjenosti, zaznani podpori učitelja ter učni uspešnosti - Košir, Katja (Psihološka obzorja (Ljubljana), 2011)
The main aim of the present research was to examine how teachers report their liking of girls and boys in different periods of schooling and how students perceive the potential differences in their teachers' preferences. Also, the differences between girls and boys in the relationship between teacher's liking and perceived teacher's support on one side and students' academic achievement on the other side were examined. 1155 students (fifth and eighth grade of elementary school and second grade of secondary school) and 50 teachers - their classteachers - participated in the study. The results show that teachers prefer girls to boys in all periods of schooling. This trend is especially evident in eight-graders. Compared to boys, girls have better academic achievement. However, there are no significant differences in the perceived teacher's support between girls and boys.
Keywords: interpersonal relations; medosebni odnosi; students; učenci; učitelji; teachers; human gender differences; razlike med spoloma; secondary schools; srednje šole; osnovne šole; primary schools; academic achievement; učna uspešnost; social perception; socialno zaznavanje; age differences; starostne razlike; teacher student interaction; odnosi med učitelji in učenci; Classroom life management; Vprašalnik življenja v razredu